Want : a novel - Strong, Lynn Steger, 1983- (Henry Holt and Company, 2020)
"Elizabeth is tired. Years after coming to New York to try to build a life, she has found herself with two kids, a husband, two jobs, a PhD--and now they're filing for bankruptcy. As she tries to balance her dream and the impossibility of striving toward it while her work and home lives feel poised to fall apart, she wakes at ungodly hours to run miles by the icy river, struggling to quiet her thoughts. When she reaches out to Sasha, her long-lost childhood friend, it feels almost harmless; one of those innocuous ruptures that exist online, in texts. But her timing is uncanny. Sasha is facing a crisis, too, and perhaps after years apart, their shared moments of crux can bring them back into each other's lives. In Want, Strong explores the subtle violences enacted on a certain type of woman when she dares to want things-and all the various violences in which she implicates herself as she tries to survive"--